How the father’s romantic relationship affects father-child brain-to-brain synchrony : a fNIRS hyperscanning study - Chong, Jezebel Chin Syuen (Nanyang Technological University, 2020)
Brain-to-brain synchrony represents a shared mental state, and this may have different implications depending on the brain region where synchrony is observed. There is ample research looking at effects of the parental romantic relationship on the parent-child relationship. However, there has not been any study looking at this on a neurophysiological level. In this study, we looked at the father’s romantic relationship in terms of romantic attachment and marital satisfaction, and how they can affect the father-child brain-to-brain synchrony when engaged in a joint task. Specifically, the father’s and child’s fNIRS data were collected as they watched animated videos together. We discovered that father-child brain-to-brain synchrony was significantly higher in the frontal right cluster brain regions for fathers high in attachment avoidance as compared to fathers low in attachment avoidance. However, fathers’ marital satisfaction was not significantly associated with brain-to-brain synchrony. The frontal right cluster includes the anterior prefrontal cortex (aPFC), middle frontal gyrus (MFG), and pars orbitalis of the inferior frontal cortex (IFC). These are brain areas involved in relational integration, processing of cognitive information and working memory, which are most likely activated during viewing of the videos. Our findings seem to suggest that fathers with an avoidant romantic attachment style tend to pay less attention to their child during the joint task and pay more attention to the videos instead, resulting in greater brain-to-brain synchrony. We hope this study could inspire future studies to continue shedding light on how aspects of parental romantic relationship can affect parent-child dyadic synchrony.